THE IMPACT OF ECONOMIC LITERACY ON ENTREPRENEURSHIP INTENTION (Third Sector Social Economic Review, 2019)
Entrepreneurs are one of the most important factors for the realization of the economic targets of countries. Economic literacy helps entrepreneurs in making right decisions and by this way causes increase in wealth of entrepreneurs and society. Additionally, it increases self-confidence of entrepreneur candidates. In this perspective, being economic literant is important for entrepreneurs. In this research we conducted an survey on the students of Kastamonu University Economics and Administrative Sciences Faculty. According to findings economic literacy affects entrepreneurship positively.
Keywords: Economic Education; Entrepreneurship Intention; Economic Literacy